Reviewing the prevalence of refractive errors and color blindness among commercial drivers - Ahmad, Ashnoor; Yadav, Priti; Pant, Kamal; Tripathi, Aditya; Dubey , Gaurav (International Journal Of Community Medicine And Public Health, 2024)
Road traffic crashes pose a significant global public health concern, claiming the lives of approximately 1.19 million people each year. A worrisome trend surfaces as a considerable majority of these fatalities involve vulnerable road users, encompassing not only drivers of heavy and light vehicles but also pedestrians, cyclists, and motorcyclists. Visual impairments play a significant role in these tragic events, further exacerbating the risks faced by road users. Whether due to poor eyesight or other vision-related challenges, impaired visual perception contributes to the vulnerability of individuals on the road. This review aimed to systematically analyze the currently available research and articles to determine the prevalence of color vision defects and refractive errors among commercial drivers. The primary objective was to investigate whether refractive errors and color vision defects pose a risk factor for road safety among commercial drivers. A primary search of databases including PubMed, Google Scholar, and others was conducted using relevant keywords. Articles published between 2010 and 2023 were considered, resulting in 16 cross-sectional studies being included for analysis. Prevalence rates were calculated using weighted averages based on sample sizes. Among commercial drivers, the prevalence of color vision impairment was lower (4.35%) compared to refractive errors (23.42%). Individuals with protanopia were at higher risk of road traffic accidents (RTAs). Complex issues such as alcoholism and visual impairments contributed to higher RTA frequencies in certain populations, emphasizing the multifaceted nature of road safety challenges.